(untitled) (Web of Teachers: Inderscience Research, 2024)
It outlines that for every nation, its mother tongue is dear, prestigious and beautiful. The language of each nation reflects its spiritual world. Literature is an art that shows the potential, wealth, and sophistication of the national language. In this sense, language and literature are one body and soul, they cannot be imagined separately. The development of the national language and literature serves the cultural development of the nation.